Association of increased duration of legislated paid maternity leave with childhood diarrhoea prevalence in low-income and middle-income countries: difference-in-differences analysis. Issue 5 (28th February 2020) - Chai, Yan; Nandi, Arijit; Heymann, Jody
Abstract : Background: Diarrhoea is the second-leading infectious cause of death in children younger than age 5 years. The global burden of severe diarrhoeal disease is concentrated in Africa and Southeast Asia, where a significant percentage of the population resides in low-resource settings. We aimed to quantitatively examine whether extending the duration of legislated paid maternity leave affected the prevalence of childhood diarrhoea in low-income and middle-income countries (LMICs). Methods: We merged longitudinal data measuring national maternity leave policies with information on the prevalence of bloody diarrhoea related to 884 517 live births occurring between 1996 and 2014 in 40 LMICs that participated at least twice in the Demographic and Health Surveys between 2000 and 2015. We used a difference-in-differences approach to compare changes in the percentage of children with bloody diarrhoea across eight countries that lengthened their paid maternity leave policy between 1995 and 2013 to the 32 countries that did not. Results: The prevalence of bloody diarrhoea in the past 2 weeks was 168 (SD=40) per 10 000 children under 5 years in countries that changed their policies and 136 (SD=15) in countries that did not. A 1-month increase in the legislated duration of paid maternity leave was associated with 61 fewer cases of bloody diarrhoea (95% CI −98.86 to − 22.86) per 10 000 children under 5 years of age, representing a 36% relative reduction. Conclusion: Extending the duration of paid maternity leave policy appears to reduce the prevalence of bloody diarrhoea in children under 5 years of age in LMICs.